Indonesia Dalam Poros Maritim Dunia dan Kapal Induk Sebagai Kunci Dari Diplomasi Maritim - Muhammad Granit Ady Wirasisya; Arnold Arswenda Kusuma (Universitas Islam Darul Ulum Lamongan, 2025)
This paper examines the strategic position of aircraft carriers within modern naval power doctrine and their relevance to Indonesia’s Global Maritime Fulcrum (GMF) framework amidst the shifting dynamics of the Indo-Pacific region. Rooted in the conceptualization of the oceans as global commons and the escalating global economic reliance on stable Sea Lines of Communication (SLOCs), this article posits sea power and naval diplomacy as pivotal strategic instruments in contemporary international relations. Utilizing a qualitativeanalytical approach based on literature and policy reviews, the discussion focuses on the evolution of the Carrier Strike Group concept, the rise of light aircraft carriers and multipurpose amphibious platforms (LHD/LHA), the integration of unmanned systems, and the strategic challenges presented by Anti-Access/Area Denial (A2/AD) capabilities and hypersonic missile technology. The analysis indicates that while aircraft carriers retain strategic value as instruments of power projection, deterrence, and maritime diplomacy, their vulnerability in high-intensity conflicts—combined with substantial procurement and operational costs—limits their relevance for non-great powers. For Indonesia, the aircraft carrier is no longer viewed as an urgent defense requirement but rather as an optionalstrategic instrument of maritime diplomacy. Specifically, light carriers or multi-purpose platforms could support regional stability and non-war operations, thereby enhancing Indonesia’s stature as an active and responsible maritime actor in the Indo-Pacific, in alignment with its